Facilities Re-layout of “X” Health Center - Dini Yulianti; Tombak Gapura Bhagya; Didi Kusvendi (Universitas Insan Cendekia Mandiri, 2023)
Public health center as the first place to carry out tracer of covid-19 survivors and theimplementation of the COVID-19 mass vaccine as well as the large interest of the people who carry out treatment at the Public health center, the Public health center is a very risky place for the spread of infectious diseases, especially covid-19. In order to minimize the effect of transmission on infectious diseases and optimize the layout of the facilities, it is necessary to improve the layout of the facilities (re-layout) of the existing Public health center services. So far, Public health center services are still very irregular, such as the distance from general medical centers to other medical centers. The purpose of this research will be to produce a new facility layout for the Public health center, so that it can optimize employee performance and the layout of the facility. In this study, the layout of the facility was redesigned using the Activity Relationship Chart (ARC) And Material Handling Costs are used to determine the distance between rooms and to estimate degree of closeness between rooms, the results of this study are two layout designs aimed at puskesmas which aim to approach the treatment center and pharmacies as well and keep the ISPA room away to minimize the spread of COVID-19 disease.